2019
DOI: 10.1016/j.freeradbiomed.2019.06.012
|View full text |Cite
|
Sign up to set email alerts
|

Redox signaling in aging kidney and opportunity for therapeutic intervention through natural products

Abstract: Kidney diseases are serious public problems with high morbidity and mortality in the general population and heavily retard renal function with aging regardless of the cause. Although myriad strategies have been assigned to prevent or harness disease progression, unfortunately, thus far, there is a paucity of effective therapies partly due to an insufficient knowledge of underlying pathological mechanisms, indicating deeper studies are urgently needed. Additionally, natural products are increasingly recognized … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 162 publications
1
14
0
Order By: Relevance
“…Nicotinamide adenine dinucleotide phosphate oxidase (NOX), transforming growth factor-β (TGF-β), NF-κB and nuclear factor-erythroid 2 related factor 2 (Nrf2) are prominent mediators of oxidative stress [ 97 ], which play important roles in regulating AD development. NOX is the primary source of fibrillar Aβ-induced ROS generation, suggesting the elimination of Aβ-induced oxidative damage by inhibiting NOX may provide an attractive therapeutic target for AD treatment [ 98 ].…”
Section: The Potential Association Between Redox Signaling and Metabomentioning
confidence: 99%
“…Nicotinamide adenine dinucleotide phosphate oxidase (NOX), transforming growth factor-β (TGF-β), NF-κB and nuclear factor-erythroid 2 related factor 2 (Nrf2) are prominent mediators of oxidative stress [ 97 ], which play important roles in regulating AD development. NOX is the primary source of fibrillar Aβ-induced ROS generation, suggesting the elimination of Aβ-induced oxidative damage by inhibiting NOX may provide an attractive therapeutic target for AD treatment [ 98 ].…”
Section: The Potential Association Between Redox Signaling and Metabomentioning
confidence: 99%
“…Advanced glycation end products (AGEs) and advanced oxidation protein products (AOPPs) arise from not only chronic disease conditions such as hyperglycemia and CKD but also during aging (Vlassara et al, 2009;Frimat et al, 2017). AGEs and AOPPs mainly bind to and interact with RAGE, the receptor of AGEs, which then activates downstream pathways such as TGF-β, NF-κB, mitogen-activated protein kinase (MAPK) and NAPDH oxidase (NOX) (Zhou et al, 2012;Ott et al, 2014;Chen et al, 2019). All these mediators contribute to the induction of multiple cytokines and growth factors, eventually causing premature aging and tissue damage.…”
Section: Oxidative Stressmentioning
confidence: 99%
“…Various mediators are involved in the development of CKD and may represent possible targets for therapy such as transforming growth factor (TGF)-β, nuclear factor-erythroid 2 related factor, peroxisome proliferator-activated γ receptor, IL-11 and advanced glycation endproducts 5 , 6 . Recently, studies reported involvement of miRNA in the progression of CKD progression 7 .…”
Section: Introductionmentioning
confidence: 99%